Measurement of charged pion, kaon, and proton production in proton-proton collisions at root s=13 TeV - (:unkn) unknown (AMER PHYSICAL SOC, 2017)
Transverse momentum spectra of charged pions, kaons, and protons are measured in proton-proton collisions at root s = 13 TeV with the CMS detector at the LHC. The particles, identified via their energy loss in the silicon tracker, are measured in the transverse momentum range of p(T) approximate to 0.1-1.7 GeV/c and rapidities vertical bar y vertical bar < 1. The pT spectra and integrated yields are compared to previous results at smaller ffiffiffi root s and to predictions of Monte Carlo event generators. The average pT increases with particle mass and charged particle multiplicity of the event. Comparisons with previous CMS results at root s = 0.9, 2.76, and 7 TeV show that the average pT and the ratios of hadron yields feature very similar dependences on the particle multiplicity in the event, independently of the center-of-mass energy of the pp collision.
Keywords: ANGULAR-CORRELATIONS; TRANSVERSE-MOMENTUM; PB COLLISIONS; LONG-RANGE; PP; SIDE